2021
DOI: 10.3390/jpm11050361
|View full text |Cite
|
Sign up to set email alerts
|

Falls Prevention and Quality of Life Improvement by Square Stepping Exercise in People with Parkinson’s Disease: Project Report

Abstract: Parkinson’s disease (PD) is a chronic neurodegenerative disorder that affects physical, psychological, and social quality of life. Square Stepping Exercise (SSE) is an effective balance training program to prevent falls and to stimulate cognitive function in the elderly; however, no study has analyzed the effect of SSE in people with PD. The main objective is to investigate whether the application of SSE is safe, applicable, and can improve balance, and is effective in preventing falls, improving cognitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The implementation of the SSE has been investigated in adult populations [ 42 , 43 ], as well as in other populations with pathologies such as diabetes mellitus type 2 [ 44 ], Parkinson’s [ 45 ], and fibromyalgia [ 23 ], among others. Therefore, we hypothesize that a 6-month intervention based on SSE will improve the regucalcin levels, executive function, physical fitness, balance, fall risk, fear of falling, and body composition in older people over 65 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the SSE has been investigated in adult populations [ 42 , 43 ], as well as in other populations with pathologies such as diabetes mellitus type 2 [ 44 ], Parkinson’s [ 45 ], and fibromyalgia [ 23 ], among others. Therefore, we hypothesize that a 6-month intervention based on SSE will improve the regucalcin levels, executive function, physical fitness, balance, fall risk, fear of falling, and body composition in older people over 65 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of SSE interventions has been shown to be effective in the older-adult population [28][29][30], as well as in specific populations, such as those with type 2 diabetes mellitus [33], multiple sclerosis [32], Parkinson's disease [48] or fibromyalgia [39], among others. Thus, we hypothesise that a 9-month intervention based on Tele-SSE will improve motor and cognitive skills in preschoolers.…”
Section: Discussionmentioning
confidence: 99%
“…A fall is a sudden, involuntary change in position that causes a person to land on a lower level (object, the floor, or the ground). 6 It is reported that nearly 30-40% of adults over 65 in the United States fall at least once a year. 7 Moreover, globally, one-third of community-dwelling older people experience falls each year.…”
Section: Introductionmentioning
confidence: 99%